# What's up with this integral

## Main Question or Discussion Point

how did gauss integrate this function
to obtain the values of the normal distribution? #### Attachments

• 1.1 KB Views: 282

arildno
Homework Helper
Gold Member
Dearly Missed
By a sequence of clever tricks:

1. Let us consider the integral
$$I=\int_{-\infty}^{\infty}e^{-x^{2}}dx$$
Now, since a dummy variable's name is irrelevant, we may write:
$$I^{2}=(\int_{-\infty}^{\infty}e^{-x^{2}}dx)^{2}=(\int_{-\infty}^{\infty}e^{-x^{2}}dx)(\int_{-\infty}^{\infty}e^{-x^{2}}dx)=(\int_{-\infty}^{\infty}e^{-x^{2}}dx)(\int_{-\infty}^{\infty}e^{-y^{2}}dy)$$
2. By Fubini's theorem, we have:
$$\int_{-\infty}^{\infty}e^{-x^{2}}dx\int_{-\infty}^{\infty}e^{-y^{2}}dy=\int_{-\infty}^{\infty}\int_{-\infty}^{\infty}e^{-x^{2}}e^{-y^{2}}dxdy=\int_{-\infty}^{\infty}\int_{-\infty}^{\infty}e^{-(x^{2}+y^{2})}dxdy$$
3. Switching to polar coordinates, $x=r\cos\theta,y=r\sin\theta,0\leq{r}\leq\infty,0\leq\theta\leq{2\pi}$, we get:
$$\int_{-\infty}^{\infty}\int_{-\infty}^{\infty}e^{-(x^{2}+y^{2})}dxdy=\int_{0}^{\infty}\int_{0}^{2\pi}re^{-r^{2}}d\theta{d}r$$
which is easily integrated to the value $\pi[/tex] 4. Hence, we have [itex]I^{2}=\pi\to{I}=\sqrt{\pi}$

Last edited:
HallsofIvy
Homework Helper
But since the question was
how did gauss integrate this function
to obtain the values of the normal distribution? The answer is "numerically". In general it is impossible to find a closed form (elementary) anti-derivative but one certainly can do a numerical integration- that's how the values in a "Gaussian distribution" table are calculated.

arildno
Homework Helper
Gold Member
Dearly Missed
Blarrgh, you read it weller than me!
I LIKE those tricks..  By a sequence of clever tricks:

1. Let us consider the integral
$$I=\int_{-\infty}^{\infty}e^{-x^{2}}dx$$
Now, since a dummy variable's name is irrelevant, we may write:
$$I^{2}=(\int_{-\infty}^{\infty}e^{-x^{2}}dx)^{2}=(\int_{-\infty}^{\infty}e^{-x^{2}}dx)(\int_{-\infty}^{\infty}e^{-x^{2}}dx)=(\int_{-\infty}^{\infty}e^{-x^{2}}dx)(\int_{-\infty}^{\infty}e^{-y^{2}}dy)$$
2. By Fubini's theorem, we have:
$$\int_{-\infty}^{\infty}e^{-x^{2}}dx\int_{-\infty}^{\infty}e^{-y^{2}}dy=\int_{-\infty}^{\infty}\int_{-\infty}^{\infty}e^{-x^{2}}e^{-y^{2}}dxdy=\int_{-\infty}^{\infty}\int_{-\infty}^{\infty}e^{-(x^{2}+y^{2})}dxdy$$
3. Switching to polar coordinates, $x=r\cos\theta,y=r\sin\theta,0\leq{r}\leq\infty,0\leq\theta\leq{2\pi}$, we get:
$$\int_{-\infty}^{\infty}\int_{-\infty}^{\infty}e^{-(x^{2}+y^{2})}dxdy=\int_{0}^{\infty}\int_{0}^{2\pi}re^{-r^{2}}d\theta{d}r$$
which is easily integrated to the value $\pi[/tex] 4. Hence, we have [itex]I^{2}=\pi\to{I}=\sqrt{\pi}$ arildno,you are a mean green integration machine Last edited:
But whats happend if I want to know the integral from 0 to x. specifically from 0 to 2

arildno
Homework Helper
Gold Member
Dearly Missed
then you should read HallsofIvy's post once more.

HallsofIvy
Homework Helper
You could look it up in a table of the "Error function", Erf(x). That is the "anti-derivative" of $e^{-x^2/2}$ and is derived, just as I said, by numerical integration.

Gib Z
Homework Helper
If you encounter a table of values for the Error function, don't quickly take that as your value for the integral.

$$Erf(x)=\frac{2}{\sqrt{\pi}}\int_0^x e^{-t^2} dt$$

HallsofIvy
Right. You will need to use the given values of $\mu$ and $\sigma$ to convert to the "standard z" variable.